Contrast Media Induced Kounis Syndrome: A Case Report - Da-Sen Chien; Andy Po-Yi Tsai; Po-Chen Lin; Giou-Teng Yiang; Meng-Yu Wu (Diagnostics, 2019)
Kounis syndrome is a rare anaphylactic reaction leading to coronary spasm, acute plaque rupture, or intrastent stenosis. Many types of medicine or environmental factors can potentially trigger Kounis syndrome by mast cell allergic reactions. In severe Kounis syndrome, reduced blood pressure or cardiac arrest may be accompanying symptoms. The treatment strategy for Kounis syndrome is usually difficult due to both cardiac dysfunction and allergic reactions. The delay to intervention to break the vicious circle may cause catastrophic complications. Therefore, early diagnosis is critical for physicians to outline detailed etiology for prevention and treat the cardiac and allergic symptoms in a timely manner. Here, we describe a case presenting rare severe Kounis syndrome with cardiac arrest which occurred after the administration of a contrast media.